The Europeanization of Europe: Europe's Cultural Identity in the Context of the Integration Processes - Mazurkiewicz, Piotr, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025, 2025)
A Bolivian, working in Warsaw for many years, decided to apply for Polish citizenship. He was asked only one question at the migration office: whether he ate sauerkraut hunters' stew and fermented dill cucumbers in brine. "You know," he said later, "for many years I was not able to swallow it, but recently I forced myself and was able to honestly answer 'yes'." Cuisine, no doubt, is one of the elements of national culture. The question, however, was not just about cuisine, but about belonging to a national community that this man found worthy of such a sacrifice. Europe is called "the continent of culture." In the book, Piotr Mazurkiewicz engages in a reflection on what constitutes the hard core of this culture which allows us to call ourselves Europeans.